Analisis Kemampuan Pemecahan Masalah Berdasarkan Tingkat Kemampuan Peserta Didik pada Fase D - Aisyah Nabilah Rusvi (DIDAKTIKA, 2024)
This study investigates the problem-solving abilities of seventh-grade students at SMP Muhammadiyah 1 Gresik in the context of flat-sided spatial figures. Employing a qualitative descriptive approach, the study involved three subjects representing varying levels of problem-solving abilities: excellent, moderate, and low. Data collection was conducted through tests, observations, and in-depth interviews. The findings revealed a range of problem-solving abilities among the three subjects. The student with excellent problem-solving skills demonstrated the ability to comprehend the problem, employ clear and rational strategies, construct accurate mathematical models, and thoroughly check their answers. The subject with moderate problem-solving skills exhibited an understanding of the problem and utilized rational strategies; however, they faced challenges in creating accurate models and drawing conclusions. The subject with low problem-solving skills encountered difficulties in comprehending the problem, selecting appropriate strategies, and correctly solving the problem. The study's conclusions emphasize the need for specialized attention and guidance for students with low problem-solving abilities to foster their effective problem-solving skills. Conversely, students with high problem-solving abilities can be provided with more complex challenges to optimize their capabilities. This research provides a foundation for teachers to tailor their support to students' individual problem-solving abilities in mathematics.